"Censorship is Official Critique": Contesting the Limits of Scholarship in the Censorship of the Hallische Jahrbücher. Issue 2 (9th July 2014) - Bunn, Matthew
Abstract : While censorship touched upon the careers of every German writer in the nineteenth century, a few cases stood out to contemporaries, defining their era. If the Demagogenverfolgung stamped the early 1820s and the prohibition of Young Germany the 1830s, the assault on left-wing or "Young" Hegelianism in 1842–43 was the major censorship case of the decade. Banning the Deutsche Jahrbücher, Rheinische Zeitung, and Leipziger Allgemeine Zeitung was part of a significant, coordinated effort to undermine a small but influential faction of radical social critics. This wave of intellectual persecution radicalized the left, sowing the seeds for Marx's thoroughgoing assault on the foundations of European state and society. Understanding these cases in the context of a broader process of the transformation of censorship practices in modern Germany, however, remains an incomplete project for historians.